Strategic Insight and Age-Related Goal-Neglect Influence Risky Decision-Making - Westbrook, Andrew; Martins, Bruna; Yarkoni, Tal; Braver, Todd S. (Frontiers in Neuroscience, 2012)
Maximizing long-run gains often requires taking on some degree of risk, yet decision-makers often exhibit risk aversion (RA), rejecting risky prospects even when these have higher expected value than safer alternatives. We investigated whether explicit strategy instruction and practice can decrease prepotent RA, and whether aging impacts the efficacy of such an intervention. Participants performed a paired lottery task with options varying in risk and magnitude, both before and after practice with a similar task that encouraged maximization of expected value and instruction to use this strategy in risky decisions. In both younger and older adults, strategy training reduced RA. Although RA was age-equivalent at baseline, larger training effects were observed in younger adults. These effects were not explained by risk-related (i.e., affective) interference effects or computation ability, but were consistent with a progressive, age-related neglect of the strategy across trials. Our findings suggest that strategy training can diminish RA, but that training efficacy is reduced among older adults, potentially due to goal-neglect. We discuss implications for neural mechanisms that may distinguish older and younger adults’ risky decision-making.